2012
DOI: 10.1093/chemse/bjs055
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value-Dependent and Nutritional Value-Independent Effects on Drosophila melanogaster Larval Behavior

Abstract: Gustatory stimuli allow an organism not only to orient in its environment toward energy-rich food sources to maintain nutrition but also to avoid unpleasant or even poisonous substrates. For both mammals and insects, sugars-perceived as "sweet"-potentially predict nutritional benefit. Interestingly, even Drosophila adult flies are attracted to most highpotency sweeteners preferred by humans. However, the gustatory information of a sugar may be misleading as some sugars, although perceived as "sweet," cannot be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 52 publications
3
73
0
Order By: Relevance
“…Indeed, we found that larval starvation impacted adult feeding behavior, measured as the gustatory perception of sugar. Gustatory perception is critical for animal survival, perhaps especially in a low-nutrient environment (Linford et al, 2015), as it helps an organism locate energy-rich food sources in order to maintain adequate nutrition (Drewnowski, 2000;Rohwedder et al, 2012). In our study, we observed reduced gustatory perception in the adult bees that experienced starvation as larvae.…”
Section: Discussion Adaptive Responses To An Anticipatory Starvationsupporting
confidence: 47%
“…Indeed, we found that larval starvation impacted adult feeding behavior, measured as the gustatory perception of sugar. Gustatory perception is critical for animal survival, perhaps especially in a low-nutrient environment (Linford et al, 2015), as it helps an organism locate energy-rich food sources in order to maintain adequate nutrition (Drewnowski, 2000;Rohwedder et al, 2012). In our study, we observed reduced gustatory perception in the adult bees that experienced starvation as larvae.…”
Section: Discussion Adaptive Responses To An Anticipatory Starvationsupporting
confidence: 47%
“…To address the effect of quinine in different larval behaviors, we assessed the naive behavior of wild type CantonS larvae for quinine-dependent choice behavior, quinine-dependent feeding, survival on quinine, and quinine-reinforced associative olfactory learning [a detailed description of the methods is also given in Rohwedder et al (2012)].…”
Section: Resultsmentioning
confidence: 99%
“…To test for quinine-dependent choice behavior, naive larvae were allowed for 5 min to choose between pure agarose and agarose containing quinine (El-Keredy et al, 2012; Rohwedder et al, 2012). Quinine concentrations ranged from 0 to 6 mM (Figure 1A), the latter being the highest soluble quinine concentration dissoluble in 2.5% agarose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory stimuli as well as light can be used as a conditioned stimulus to be associated with either reward or punishment (unconditioned stimulus). Rewarding stimuli include sugar and low concentrations of salt; punishing stimuli comprise high concentrations of salt, quinine, electric shock, heat, mechanical stimulation through vibration (buzz) and light 11,12,[17][18][19][20][21][22][23][24] . Click here to view larger figure.…”
Section: Figurementioning
confidence: 99%